Effects of sorghum, purple rice and rhubarb rice on lipids status and antioxidant capacity in mice fed a high-fat diet. (December 2017) - Shen, Yingbin; Song, Xun; Chen, Yongsheng; Li, Li; Sun, Jian; Huang, Caihuan; Ou, Shiyi; Zhang, Hui
Highlights: Sorghum bicolor (L.) Moench showed highest in phenolic and flavonoid content. Sorghum bicolor (L.) Moench exhibited highest antioxidant activities in vitro . Sorghum bicolor (L.) Moench significantly improved the in vivo antioxidant status. Supplementation of sorghum was highly effective in regulating lipid status in vivo . Abstract: Epidemiological evidence suggests that whole grain intake is associated with reduced risk of oxidative stress-related chronic disease. It remains unclear that whole grains can improve antioxidant activity in vivo . This study was to investigate the hypolipidemic and antioxidant capability of sorghum, purple rice and rhubarb rice. Our results indicated that sorghum contained the highest total phenolic content, total flavonoid content and total anthocyanin content, and had highest free radical scavenging activity and reducing power than those of the purple rice and rhubarb rice in vitro . Compared with high fat diet group, animals feeding with sorghum had a 24.47% reduction in serum cholesterol, 32.72% reduction in triglyceride, and 27.27% increase in high-density lipoprotein cholesterol, respectively ( p < 0.05). Sorghum was more effective than purple rice and rhubarb rice in improving in vivo antioxidant and lipid profile. These results suggested that sorghum could be used for the prevention of oxidative stress-related chronic diseases.